Drosophila divalent metal ion transporter Malvolio is required in dopaminergic neurons for feeding decisions. - Søvik, E.; LaMora, A.; Seehra, G.; Barron, A.B.; Duncan, J.G.; Ben-Shahar, Y. (Genes, Brain, and Behavior, 2017)
Members of the natural resistance-associated macrophage protein (NRAMP) family are evolutionarily conserved metal ion transporters that play an essential role in regulating intracellular divalent cation homeostasis in both prokaryotes and eukaryotes. Malvolio (Mvl), the sole NRAMP family member in insects, plays a role in food choice behaviors in Drosophila and other species. However, the specific physiological and cellular processes that require the action of Mvl for appropriate feeding decisions remain elusive. Here, we show that normal food choice requires Mvl function specifically in the dopaminergic system, and can be rescued by supplementing food with manganese. Collectively, our data indicate that the action of the Mvl transporter affects food choice behavior via the regulation of dopaminergic innervation of the mushroom bodies, a principle brain region associated with decision-making in insects. Our studies suggest that the homeostatic regulation of the intraneuronal levels of divalent cations plays an important role in the development and function of the dopaminergic system and associated behaviors.